Student engagement and final year project achievement in the Peninsular Malaysia Agricultural Vocational College - T Nor, Ku Mahiran; Kang, Enio Mohd Sufian; Jamaluddin, Rahimah; Mohd Puad, Mohd Hazwan (Horizon Research Publishing, 2023)
This study aims to determine the level of student involvement and its influence on the achievement of the final year project (PTA) at the Agricultural Vocational College (KV) in Peninsular Malaysia. The study used a descriptive correlational design, which involved a total of 136 students from 3 agricultural KVs using simple random sampling techniques. Survey questionnaires are used as study instruments. The respondents needed to answer 30 items divided into sub-constructs that were divided into emotional, behavioral, skills and cognitive items. The findings showed that overall, the involvement of Malaysian Vocational Diploma students in the implementation of final year projects was at a high level (M=3.95 and SD=.421). The achievement level of most students in PTA at agricultural KV in Peninsular Malaysia was found to be at an excellent level (grade A) of 69.1%. Correlation analysis shows that student involvement in emotional and behavioral dimensions has a significant relationship with student PTA achievement. However, for the cognitive dimension, there is no significant association with students' PTA achievement. Measures should be taken by various parties to enhance student's engagement as well as to improve agricultural students' achievements in vocational college for the betterment of this field of study.